Safety and Efficacy of Epi-Bowman Keratectomy in Photorefractive Keratectomy and Corneal Collagen Cross-Linking: A Pilot Study. (3rd May 2016) - Shetty, Rohit; Nagaraja, Harsha; Pahuja, Natasha Kishore; Jayaram, Tejal; Vohra, Vishal; Jayadev, Chaitra
Abstract: Purpose : The purpose of this study is to compare the efficacy and safety of Epi-Bowman Keratectomy (EBK) using Epi-clear™ epikeratome with a mechanical scraper for corneal epithelium debridement during photorefractive keratectomy (PRK) and corneal collagen cross-linking (CXL). Methodology : Sixty eyes of 30 patients undergoing PRK and 44 eyes of 44 patients undergoing CXL were included in this study. In the PRK group, one eye of each patient underwent EBK and the other eye epithelial debridement with a mechanical scraper. In the CXL group, 22 eyes of 22 patients underwent EBK and the other 22 eyes with a mechanical scraping to remove the epithelium. Intra-operative spectral domain optical coherence tomography (SD OCT; Bioptigen Inc, Durham, NC) was performed to evaluate the integrity of Bowman's membrane following epithelial removal. The time taken for epithelial removal, post-operative pain score using the Wong-Baker's pain scale, time for epithelial healing, and the epithelial profile using the Optovue (Optovue Inc. Fremont, CA) during the healing was observed and analyzed between the two groups and subgroups. Results : Intra-operative SD OCT showed a smooth and undamaged Bowman's membrane when EBK was performed. Post-operative pain was significantly less ( p < 0.01 in the PRK group and p < 0.001 in the CXL group) with faster epithelial healing ( p < 0.001 in the PRK group and p < 0.0001 in the CXL group) in the EBK subgroup as compared with the mechanical scraper subgroup. Epithelial profiling during the healing phase showed an edematous epithelium in the initial 2 weeks in the mechanical scraper subgroup while the EBK subgroup showed minimal epithelial edema lasting up to a week with regularized and smooth corneal epithelium healing. Conclusion : Epi-Bowman Keratectomy appears to be an effective and safe method of corneal epithelial debridement with negligible damage to Bowman's membrane and the surrounding epithelium leading to early healing thereby reducing the post-operative pain and complications.